PENGEMBANGAN MODEL PEMBELAJARAN BERBASIS INTUISI UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF DALAM MEMECAHKAN MASALAH MATEMATIKA SISWA KELAS X SMA NEGERI 2 SRAGEN - Lestari, Mulyaningrum; Riyadi, Riyadi; Usodo, Budi (Jurnal Pembelajaran Matematika, 2015)
Abstract: This research aimed to product model of learning based on intuition to improve the creative thinking ability in solving mathematics problems in the students of SMA N 2 Sragen validly, practically, and effectively. The learning model produced included syntax and learning tools such as teaching material, lesson plan, worksheet, and problem sheet. This type of the research was a Research and Development (R&D). Subjects of this research were students class of X MS (Mathematic Science) 4 and class X MS 5 of SMA N 2 Sragen, Central Java. The process of developing an learning model based on intuition referred to development model of Plomp and Borg & Gall including : (1) studying and collecting information in preliminary investigation stage, (2) designing an learning model based on intuition, created learning tools (teaching material, lesson plan, worksheet, and problem sheet), (3) realizing model and learning tools organized into first draft, (4) validating the first draft against validator, revising, and then trying out the model, and revising again, and (5) holding FGD to evaluate the results of tryout that had been conducted and revising it for the next tryout. This research produced syntax and learning tools (teaching material, lesson plan, worksheet, and problem sheet) of learning model based on intuition to improve the creative thinking ability in solving mathematics problems of students validly, practically, and effectively. The procedure of syntax in an learning model based on intuition: (1) The teacher made introduction such as preparing the students psychically and physically, apperception, providing motivation and learning objectives, (2) Teacher divided the students heterogeneously into some groups of two, (3)The students were given worksheet to discuss in group and there were five activities observing; questioning; exploring; associating; and communicating, (4) The students were given problems individually in the problem sheet to work on with stages that could appear intuition and improve their creative thinking ability including beginning, incubation, illumination, and verification, (5) Closing such as included reflection and homework.Keywords : model development, learning model, intuition, creative thinking ability